Validation of the Simplified Disease Activity Index (SDAI) with a quick quantitative C-reactive protein assay (SDAI-Q) in patients with rheumatoid arthritis: a prospective multicenter cross-sectional study. (August 2022) - Schally, Julia; Brandt, Henning Christian; Brandt-Jürgens, Jan; Burmester, Gerd R.; Haibel, Hildrun; Käding, Henriette; Karberg, Kirsten; Lüders, Susanne; Muche, Burkhard; Protopopov, Mikhail; Rios Rodriguez, Valeria; Torgutalp, Murat; et al.
Objectives: The Simplified Disease Activity Index (SDAI) is a recommended composite score for assessing the remission status in patients with rheumatoid arthritis (RA). However, determination of C-reactive protein (CRP) levels takes several hours and sometimes days and limits the use of the SDAI in the clinical setting. The aim of this study was to validate the SDAI using a quick quantitative C-reactive protein (qCRP) assay (as SDAI-Q) in RA patients. Design: This is a multicenter, prospective, cross-sectional pilot study in RA patients. Methods: Adult patients (⩾18 years) with a clinical diagnosis of RA were recruited between January 2020 and September 2020 from five rheumatologic centers located in Berlin, Germany. SDAI, SDAI-Q, Clinical Disease Activity Index (CDAI), and DAS28 scores comprising CRP, qCRP, or erythrocyte sedimentation rate (ESR) were calculated. The agreement of disease activity categories was analyzed using cross tabulations and weighted Cohen's kappa. The agreement of numerical values was analyzed with Bland–Altman plots and intraclass correlation coefficients (ICCs). Results: Overall, 100 RA patients were included in the statistical analysis. The mean value of qCRP (7.89 ± 16.98 mg/l) was slightly higher than that of routine laboratory CRP (6.97 ± 15.02 mg/l). Comparing SDAI and SDAI-Q, all patients were assigned to identical disease activity categories. Agreement of disease activity categories by CDAI and SDAI/SDAI-Q was observed in 93% with a weighted Cohen's kappa of 0.929 (95% confidence interval (CI) = 0.878; 0.981). Conclusion: The SDAI-Q showed an absolute agreement regarding the assignment of disease activity categories in comparison with the conventional SDAI. Therefore, the SDAI-Q may facilitate the application of a treat-to-target concept in clinical trials and clinical routine as a quickly available disease activity score incorporating CRP as an objective parameter.